Assessment of sub-epidermal moisture by direct measurement of tissue biocapacitance. (November 2019) - Ross, Graham; Gefen, Amit
Highlights: The SEM Scanner measures static biocapacitance to determine moisture contents. The use of a "delta" value eliminates confounding systemic changes. Experimental results show a measurement depth of approximately 4 mm. Simulation results are consistent with the experimental results. Abstract: The noninvasive SEM Scanner technology described herein assesses the fluid contents of human skin and subdermal tissues to a depth of several millimeters. The device makes a direct steady-state measurement of the capacitance of its sensor, which is affected by the equivalent dielectric constant of the material (i.e. the layered tissue structures) that is within the electric field between the sensor electrodes. Calculation of a "delta" value that compares measurements from several sites, some of which will be healthy tissue, compensates for systemic changes and provides a consistent measure of tissue health condition. We describe the hardware, software and rigorous laboratory testing and computational modeling of the principles of operation of the SEM Scanner, for the first time in the literature. These studies revealed a detection depth of approximately 4 mm for an electric potential of 0.3 V. The novel SEM Scanner provides the first useful technological means to assess the health status of tissues below the stratum corneum in patients who are at-risk for pressure injuries.